Investigation of pelvic symmetry: A systematic analysis using computer aided design software. (8th November 2022) - Zheng, Qiubao; Xu, Kangshuai; Zhan, Xiaorui; Huang, Fuming; Wang, Liping; Chen, Sheqiang; Li, Jiacheng; Yang, Cheng; Chen, Yuhui; Fan, Shicai
Abstract: Objectives: This study aimed to investigate the symmetry of the Chinese pelvis. Methods: Computed tomography scan images of each of 50 Chinese pelvises were converted to 3D models and the left sides of the pelvises were reflected on Mimics software. Then, the reflected left side model was aligned with the right side using the closest point algorithm function of Geomagic software to perform symmetry analysis. The volume and surface area of either side of the pelvises were also calculated. The mean standard deviation (SD), the mean percentage of permissible deviations within the ±2 mm range, the percentage differences in volume and surface area were measured to compare pelvic symmetry. In addition, the distribution of pelvic bilateral symmetry associated with both age and sex were compared. Results: The mean SD was 1.15 ± 0.16 mm and the mean percentage of permissible deviations was 90.82% ± 4.67%. The deviation color maps showed that the specific areas of asymmetry were primarily localized to major muscle or ligament attachment sites and the sacroiliac joint surfaces. There was no significant difference between the bilateral sides of the pelvis in either volume or surface area. Additionally, no difference in any indexes was exhibited in relation to sex and age distribution. Conclusion: Our results demonstrated that the pelvis has high bilateral symmetry, which confirmed the potential of using contralateral pelvic models to create fully patient‐specific and custom‐made pelvic implants applicable for the treatment of fracture and bony destruction. Abstract : This investigation using computer aided design software avoided some limitations of previous studies and filled an important research gap in the literature of pelvic symmetry. The bilateral hemi‐pelvises showed a high degree of symmetry. It would be feasible and effective to apply the concept of pelvic symmetry to create fully patient‐specific and custom‐made pelvic implants by using contralateral pelvic models for the treatment of fracture and bony destruction.